Effect of Microhydration on the Peptide Backbone of N-Acetyl- Phenylalaninylamide (NAPA) Using IR, Raman and Vibrational Chiroptical Spectrosocpies (VCD, ROA): A Computational Study - Alauddin, Md.; Ripa, Joya Datta (European Journal of Applied Sciences, 2022)
In this work, N-acetyl-phenylalaninylamide (NAPA) and microhydrated NAPA i.e. [NAPA-A(H2O)n (n = 1-4)] complexes were studied with the aid of density functional theory (DFT) calculation in the gas phase to determine the absolute configuration, hydration effect on amide modes (amide I-IV), the robustness of amide modes, and associated amide modes. IR, Raman, vibrational chiroptical (VCD and ROA) spectra, VCD rotational strength, VCD dipole strength and the angle between the electric transition dipole moment (ETDM) and the magnetic transition dipole moment (MTDM) were performed using DFT/wB97XD/cc-pVTZ level of the computational approach. The absolute configuration (D/L) of the most stable conformer of NAPA (NAPA-A) was confirmed by the analysis of the VCD spectra that show opposite sign, and intensity. Amide I (C=Os) VCD bands are non-robust and amide II-IV (C-Ns, N-Hb and N-Hs) bands are robust and reliable on the basis of the robustness concept. Consequently, the VCD stretching and scissoring modes of NH2 and H2O for [NAPA- A(H2O)n (n=1-4)] complexes are also robust and reliable. On the other hand, ROA calculation confirmed that the C5 interaction in the peptide backbone of NAPA-A is entirely lost in presence of a single configuration of an explicit water molecule. [NAPA-A(H2O)1] complex has a C7 interaction in the peptide backbone which is also lost in the presence of the 2nd and 3rd water molecules. DCPI (180) Raman and DCPI (180) ROA calculations were also performed in the solution phase (implicit water) using the integral equation formalism variant polarizable continuum model (IEF-PCM) to compare the gas phase results.